(untitled) (Fiep Bulletin - online, 2015)
The chronic pain is becoming day by day a problem that affects individuals of both sex, causing physical, psychological and social disturbs that invariably affect the quality of life of the individual. Causing disarrangements in the whole nervous system. The vertebral manipulation can intervene with the regulation of the autonomous nervous system (ANS), which is divided in sympathetic nervous system (SNS) and parasympathetic nervous system (PNS). The goal of the present study was to observe the alterations caused in the autonomous nervous system after the vertebral manipulation of the dorsal sympathetic trunk in patients with chronic pain, all being analyzed by the Bio-Express. The study was carried through with 12 individuals of both sexes who presented chronic pain (for more than three months). The procedures had been carried through in the Clínica de Fisioterapia Salgado, Clinique du Sport, in Londrina-PR, using a private and sterile room for the accomplishment of the study. In the analysis of the results we observed that the PNS suffered an increase after the vertebral manipulation, going from an average of -2,20 to -1,62. The SNS suffered a reduction after the vertebral manipulation going from an average of 1,50 to 1,41. The cardiac frequency had a reduction after the vertebral manipulation going from an average of 83,6 to 79,0 with the patient lying down and an average of 95.1 to 92.9 with the patient standing. We can conclude that the vertebral manipulation of the sympathetic dorsal trunk can cause an influence on the ANS.